What is the current provision of service for gastrostomy insertion in England?. Issue 2 (6th October 2022) - Parr, Heather; Williams, Elizabeth A; White, Sean; Thompson, Nick; McAlindon, Mark E; Hopper, Andrew D; McKinlay, Alistair; Sanders, David Surendran
Abstract : Background: Significant morbidity and mortality can be associated with gastrostomy insertion, likely influenced by patient selection, indication and aftercare. We aimed to establish what current variation in practice exists and how this has improved by comparison to our previously published British Society of Gastroenterology survey of 2010. Methods: We approached all National Health Service (NHS) hospitals in England (n=198). Email and web-based questionnaires were circulated. These data were correlated with the National Endoscopy Database (NED). Results: The response rate was 69% (n=136/198). Estimated Percutaneous Endoscopic Gastrostomy (PEG) placements in the UK are currently 6500 vs 17 000 in 2010 (p<0.01). There is a dedicated PEG consultant involved in 59% of the centres versus 30% in 2010 (p<0.001). Multidisciplinary team meeting (MDT) discussion occurs in 66% versus 40% in 2010 (p<0.05). Formal aftercare provision occurs in 83% versus 64% in 2010 (p<0.001). 74/107 respondents (69%) reported feeling pressurised to authorise a gastrostomy. Conclusion: This national survey, validated by the results from NED, demonstrates a reduction of over 60% for PEG insertion rates compared with previous estimates. There has also been an increase in consultant involvement, MDT discussion and aftercare provision. However, two-third of responders described 'pressure' to insert a gastrostomy. Perhaps further efforts are needed to include and educate other specialty teams, patients and next of kin.